SIMS study of deuterium distribution and thermal stability in ZMR SOI structures - Boutry-Forveille, A.; Ballutaud, D.; Nazarov, A.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
SIMS measurements and thermal effusion experiments were performed to study the distribution and thermal stability of deuterium in SOI structures fabricated by zone melting recrystallization technique. It was found that the disordered structure at the silicon-buried oxide interfaces is directly related to the distribution of deuterium in the SOI system. The diffusion coefficient of deuterium in the top silicon layer at 250°C was determined. For the first time, the high-temperature (up to 600°C) stability of deuterium in the buried oxide was demonstrated, without any diffision into silicon layers.